How Much Should Consumers with Mild to Moderate Hearing Loss Spend on Hearing Devices? - Vinaya Manchaiah; Steve Taddei; Abram Bailey; De Wet Swanepoel; Hansapani Rodrigo; Andrew Sabin (Audiology Research, 2025)
Background: This study examined the relationship between hearing device price and sound quality. Method: A novel consumer-centric metric of sound quality (“SoundScore”) was used to assess hearing devices’ audio performance. Each hearing device is tested with two fittings. The “Initial Fit” is designed to approximate the most likely fitting for an individual with a mild-to-moderate sloping sensorineural hearing loss. The “Tuned Fit” includes adjusting parameters optimized to hit prescriptive fitting targets (NAL NL2) on an acoustic manikin. Each fitting is evaluated across five dimensions. Both fittings are combined using a weighted average to create a single number from 0 to 5 representative of a device’s overall audio performance. Seventy-one hearing devices were tested. Results: A strong positive correlation was found between hearing device price and SoundScore. The average SoundScore increased dramatically as the price approached USD 1000, with marginal improvements beyond this point. SoundScore was consistently poor for devices under USD 500, highly variable between USD 500–1000, and consistently good over USD 1000. Conclusions: There is a strong but nonlinear relationship between hearing device price and sound quality. This information can aid consumers in making informed decisions while also assisting hearing healthcare professionals in providing comprehensive guidance to their patients.